Teachers’ Motivation in State Payaraman Elementary School Ogan Ilir - Mardiansyah, Mhd; Lian, Bukman; Putra, Muhammad Juliansyah (Journal of Social Work and Science Education, 2023)
The purpose of this study was to determine the motivation of teachers in public elementary schools in Payaraman District, Ogan Ilir Regency, South Sumatra. This research was conducted on teachers in Payaraman district, Ogan Ilir Regency. The sample size was taken as many as 102 teachers. The sampling technique is intended for sampling, namely where the respondents are some of the teachers in Payaraman District, Ogan Ilir Regency. Data collection was carried out by distributing questionnaires using a 5-point Likert scale to measure 25 statement items. The research method used is descriptive qualitative. Findings have shown that teachers have a high motivation to go to work and have a job as a teacher.